Targets [videorecording (DVD)] - Bogdanovich, Peter, 1939-2022; Platt, Polly; Karloff, Boris, 1887-1969; O'Kelly, Tim; Hsueh, Nancy, 1941-1980; Brown, James, 1920-1992; Peterson, Arthur, 1912-1996; Jackson, Mary, 1910-2005; Morgan, Tanya (Actress); Baron, Sandy, 1936-2001; Kovacs, Laszlo, 1933-2007 (Criterion collection, 2023)
Old Hollywood collides with New Hollywood, and screen horror with real-life horror, in the startling debut feature from Peter Bogdanovich. The chillingly prescient vision of American-made carnage casts Boris Karloff as a version of himself: an aging horror movie icon whose fate intersects with that of a seemingly ordinary young man on a psychotic shooting spree around Los Angeles. Charged with provocative ideas about the relationship between mass media and mass violence.